2022
DOI: 10.1016/j.nicl.2021.102935
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the structure-function relationship of the corticomotor system early after stroke using machine learning

Abstract: Highlights MRI metrics can classify MEP status with 81% accuracy using support vector machine. Metrics from both T1 and diffusion MRI are important for this classification. Machine learning is a powerful tool for analysing multivariate MRI data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 45 publications
(63 reference statements)
0
2
0
Order By: Relevance
“…Subsequently, the model can be recalled using only partial NI variables or time points to predict the recovery trajectory of the same patient or a new stroke patient. This capability can assist clinicians in personalized treatment planning and rehabilitation strategies [23,24].…”
Section: Potential Applications Of the Proposed Stam-ni Classificatio...mentioning
confidence: 99%
“…Subsequently, the model can be recalled using only partial NI variables or time points to predict the recovery trajectory of the same patient or a new stroke patient. This capability can assist clinicians in personalized treatment planning and rehabilitation strategies [23,24].…”
Section: Potential Applications Of the Proposed Stam-ni Classificatio...mentioning
confidence: 99%
“…Veerle found that the model created was capable of producing an average AUC value of 0.76 for eye movement features. Chong [21] conducted research related to stroke to investigate the relationship between the structure and function of the corticomotor system early after stroke using machine learning. Chong obtained research results in the form of an SVM classification model with an 81% accuracy in detecting motor generating potential, although false positives were more common than false negatives.…”
Section: Introductionmentioning
confidence: 99%